PR COMMUNICATION STRATEGY IN HANDLING B3 WASTEIN THE COMPANY PT. SATRIA JAYA SENTOSA KOLAKA DISTRICT, SOUTHEAST SULAWEISI PROVINCE (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this research is to find out the communication strategy in dealing with B3 waste. At the company PT. Satria Jaya Sentosa the research method used is a qualitative descriptive research method. This research lasted for one month located in kolaka subdistrict Baula data collection techniques through text observation, interviews and documentations. The results of this study show that waste is unwanted residual material after the end of a process. Waste is determined by humans according to the degree of its use in actual natural processes. B3 waste processing must be carried out in an integrated manner, because improper management of B3 waste can cause harm to human life, other living things and damage to the environment. The company PT. Satria Jaya Sentosa is a mining company that B3 waste processing process from start to finish,